Determination of Synthetic Phenolic Antioxidants in Vegetable Oil and Oil-Enriched Foods by High-Performance Liquid Chromatography with Electrochemical Detection. (4th March 2017) - Sun, Zheng; Wang, Meng; Cheng, Ni; Gao, Hui; Deng, Jianjun; Zhao, Jing; Cao, Wei
ABSTRACT: Three synthetic phenolic antioxidants, tertiary butyl hydroquinone, butylated hydroxytoluene, and butylated hydroxyanisole, were determined in vegetable oil and oil-enriched food by high-performance liquid chromatography (HPLC) with electrochemical detection. The separation was achieved using a reverse-phase column and gradient elution with methanol and 1% acetic acid. The limits of detection and quantification of the analytes were 2–120 lower, higher than those obtained by diode-array detection. The recoveries were 103.3% for tertiary butyl hydroquinone, 97.3% for butylated hydroxyanisole, and 95.2% for butylated hydroxytoluene. The results showed that HPLC with electrochemical detection is suitable for the quantification of low concentrations of phenolic antioxidants in vegetable oil and oil-enriched food with high sensitivity and accuracy.